2014
DOI: 10.1155/2014/629187
|View full text |Cite
|
Sign up to set email alerts
|

Latex Hypersensitivity among Allergic Egyptian Children: Relation to Parental/Self Reports

Abstract: Background. Latex allergy is one of the major health concerns and allergic reactions to latex may be serious and fatal. Purpose. In this study, we sought to determine the frequency of latex hypersensitivity in a group of allergic Egyptian infants and children and its relation to the history provided by the patients or caregivers. Methods. We consecutively enrolled 400 patients with physician diagnosed allergic diseases. The study measurements included clinical evaluation for the site and duration of allergy, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…During school activities, children could be exposed in a non-obvious way to potential allergens hidden in nondietary sources, reporting apparently unexplainable chronic allergic symptoms. Examples are the plasticine that contains wheat, the stuffed animals that can be made with crushed or ground nut shells, finger paint containing wheat, milk, corn and oat, crayons containing soy, dustless chalk containing casein, and balloons manufactured with natural rubber latex [86]. Alternative materials and precautions should be used to avoid potential reactions for allergic children.…”
Section: Management and Preventionmentioning
confidence: 99%
“…During school activities, children could be exposed in a non-obvious way to potential allergens hidden in nondietary sources, reporting apparently unexplainable chronic allergic symptoms. Examples are the plasticine that contains wheat, the stuffed animals that can be made with crushed or ground nut shells, finger paint containing wheat, milk, corn and oat, crayons containing soy, dustless chalk containing casein, and balloons manufactured with natural rubber latex [86]. Alternative materials and precautions should be used to avoid potential reactions for allergic children.…”
Section: Management and Preventionmentioning
confidence: 99%
“…Studies have shown that tropical fruits (such as avocado, banana, chestnut, and kiwi) contain proteins having allergenic similarities with latex 31,32) . Patients with allergy to these fruits have high risk of cross-reactivity and develop allergy known as "latex fruit syndrome " when they come in contact with latex-derived products [32][33][34] .A pproximately 30%-50% of individuals with latex allergy show an associated hypersensitivity to one or more fruits 6,32,34) .…”
Section: Cross-reactivity With Fruitsmentioning
confidence: 99%
“…Atopy has also been reported as a risk factor for developing latex sensitization and allergy. In the general population of children, the percentage of latex sensitization is approximately 1% [ 4 ], but it increases to 3–5% in atopic children [ 26 , 27 , 28 ], with about half of them experiencing clinical manifestations ( Table 3 ).…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%